The Foreign Language Students’ Beliefs Regarding Learning Strategies In Different Kazakhstan University Students - Orynbek, Gulnar; Dauletali, Akbarkan; Farida, Orazakynkyzy; Lyailya, Koishigulova; Zhanat, Bissenbayeva (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
As we live in global village, there are several inner circle native English speakers around the world. Furthermore, there are people who live in out circle and speak English as a second language, the rest who live in expending circle and use English as a foreign language. The increase use of English as an international language more people believe that the necessity of some knowledge about English language should be known, since it provides the awareness of learners beliefs about English language learning as well as it expands the job opportunities. This study can be significant in two parts (theoretical and practical). Firstly in theoretical part this research can be a new area in English language learners’ beliefs in applied linguistics worldwide, and this study can offers information about Kazakhstan University students’ beliefs about English language learning. Secondly in practical level, this research would help EFL teachers in Kazakhstan for understanding of their students’ beliefs about English language learning, and also can be a guideline to the teachers in their teaching methods as well as for the learners understanding of their own beliefs about English language learning.